Wire-assisted modification of Havst catheter stripping of the great saphenous vein trunk - Lin, Xiaowen; Li, Pengfei; Zhuang, Lijuan (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the therapeutic outcomes using Havst catheter stripping vs. a wire-assisted modification of Havst catheter stripping the trunk of great saphenous vein (GSV) above knee.MethodsData were collected from 120 patients who underwent stripping of the GSV trunk using a Havst catheter from January 2025 to June 2025; 60 patients underwent the conventional approach to Havst catheter stripping and 60 patients underwent a wire-assisted modification of Havst catheter stripping. Age, gender, Clinical class, Stripping time of the GSV trunk (including tumescent anesthesia), length of the stripped GSV trunk above knee, intraoperative Visual Analogue Scale (VAS) pain score, and success of surgery were compared between treatment groups.ResultsA wire-assisted modification of Havst catheter stripping showed significant advantages over conventional approach of Havst catheter in terms of longer median (interquartile range, IQR) Stripping length of GSV trunk 384 (361, 407) vs. 321 (309, 334) cm, p < 0.0001, and higher success rate (96.67% vs. 76.67%, p = 0.0031), and shorter median (interquartile range, IQR) thigh incision length 11 (10, 12) vs. 12 (11, 14) cm, p = 0.0006). There were no significant differences in age (t-tests, mean ± standard deviation) (55.23 ± 10.00 vs. 54.60 ± 11.12 years, p = 0.7435), gender (p = 0.0956), Clinical class (p = 0.4395), Stripping time (t-tests, mean ± standard deviation) (410 ± 18 vs. 407 ± 17 s, p = 0.3816), intraoperative VAS pain score median (interquartile range, IQR) [(1 (1, 2) vs. 1 (1, 2), p = 0.8897].ConclusionThe wire-assisted modification of Havst catheter stripping enabled faster and the longer segment of the GSV trunk above knee was stripped compared to the conventional approach to Havst catheter stripping.